(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay addresses the issue of compulsory community treatment (CCT) in psychiatry. The existence of this legal instrument is controversial because it is arguably incompatible with the constitutional rules and the saving clause required for all mandatory health treatments. After analyzing the evolution of the institute over time, this essay focuses on the Recommendations of the Conference of the Regions (29 April 2009). The way the CCT is characterized and operationalized led to its increasing use by territorial psychiatric services.